Hubungan antara Persepsi Gaya Kepemimpinan Kepala sekolah dan Efikasi Diri dengan Kinerja Guru - Wijaya, Mr. Sadar, Dr. Taufik Kasturi, M.Si (2015)
The aim of this research is to know the relationship between the perception of headmaster leadership style and self efficacy with teacher performance. The samples in this study are Elementary school teachers in Kuwarasan district, Kebumen Regency, Central Java which totaled 98 teachers. The sample collection technique in this research is stratified cluster random sampling and data collection used scales of the perception of headmaster leadership style, self efficacy and teacher performance. The data analysis method used a multiple regression analysis. Characteristics of respondents are consisting of elementary school teachers in Kuwarasan district, Kebumen Regency, civil servants and non civil servants, employment between 5 - 35 years, a Diploma II and Bachelor degree, male and women. The results of the research: 1) there are positive relations between perception of headmaster leadership style with teacher performance, 2) there are positive relations between self efficacy with teacher performance, 3) shows that there are very significant relations between perception of headmaster leadership style and self efficacy with teacher performance. Conclusion the research is the perceptions of headmaster leadership style and self efficacy together have a positive relation with teacher performance. Implications for educational psychology science are become the evaluation and needed the role of the science of psychology in order to improve performance among teachers.